the HUBUNGAN AKTIFITAS FISIK DENGAN RISIKO PENYAKIT JANTUNG PADA REMAJA PUTRI DI SMA NEGERI 13 BOMBANA KECAMATAN MATAOLEO KABUPATEN BOMBANA - Kartini, Kartini; hasni, Hasni; asi, melania (Jurnal Stunting Pesisir dan Aplikasinya, 2025)
Introduction: Heart disease is one of the non-communicable diseases (NCDs) with the highest mortality rate worldwide and remains a serious public health problem, including in Indonesia. Currently, the risk of heart disease is not only found in adults and the elderly but is also increasing in adolescents along with lifestyle changes characterized by low physical activity. The decline in physical activity in adolescents is influenced by modernization, increased sedentary activities, and high screen time, which have an impact on the emergence of early risk factors for heart disease such as obesity, hypertension, and metabolic disorders. The purpose of this study was to determine the relationship between physical activity and the risk of heart disease in adolescent girls at SMA Negeri 13 Bombana, Mataoleo District, Bombana Regency. Methods: This study was quantitative and designed using an observational cross-sectional approach. The population was all 187 adolescent girls at SMA Negeri 13 Bombana, Mataoleo District, Bombana Regency. The sample was 65 adolescents at SMA Negeri 13 Bombana, Mataoleo District, Bombana Regency. The test tool used in the bivariate analysis was the Chi-square test. Results: %). Of the 65 respondents, the highest physical activity level among adolescent girls was in the high category (35 respondents, 53.8%), and the highest risk level among adolescent girls was in the low-risk category (45 respondents, 69.2%). There is a relationship between physical activity and the risk of heart disease in adolescent girls at State Senior High School 13 Bombana, Mataoleo District, Bombana Regency (x2 = 11.081; p-value = 0.004). Conclusion: There is a relationship between physical activity habits and the risk of heart disease in adolescent girls at State Senior High School 13 Bombana, Mataoleo District, Bombana Regency.